Results 1 to 2 of 2
Like Tree1Thanks
  • 1 Post By Prove It

Math Help - Why is 2x^2-xy-3y^2 = (2x - 3y)(x + y) ?

  1. #1
    kkm
    kkm is offline
    Newbie
    Joined
    Jul 2010
    Posts
    16

    Why is 2x^2-xy-3y^2 = (2x - 3y)(x + y) ?

    Why is 2x^2-xy-3y^2 = (2x - 3y)(x + y) ? What kind of factorization is used here?
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Prove It's Avatar
    Joined
    Aug 2008
    Posts
    11,592
    Thanks
    1445

    Re: Why is 2x^2-xy-3y^2 = (2x - 3y)(x + y) ?

    It looks like a factorisation by grouping...

    \displaystyle \begin{align*} 2x^2 - xy - 3y^2 &= 2x^2 - 3xy + 2xy - 3y^2 \\ &= x(2x - 3y) + y(2x - 3y) \\ &= (2x - 3y)(x + y) \end{align*}
    Thanks from kkm
    Follow Math Help Forum on Facebook and Google+

Search Tags


/mathhelpforum @mathhelpforum